Factor Analysis of the Challenges and Strategies for Effective Work-Based Learning in Nigerian Technical and Vocational Education - Rabiu Haruna; Yusri Bin Kamin (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
This study investigated challenges and strategies for effective work-based learning in Nigerian technical and vocational education (TVE) using a factor analysis approach. Through the use of structured questionnaire, the opinions of 385 respondents consisting of 227 TVE lecturers and 158 supervisors of technical and vocational firms were sought. The data collected were analyzed using descriptive statistics and varimax rotated principal component factor analysis with factor loading of 0.40. The result showed that about 25% of the TVE firms in Northwest Nigeria are industrial technical firms, 22% are computer/ICT, 19% are business/distributive trade, 18 % are home economics while about 16% are agricultural based. Using principal component factor analysis, the study identified: policy, funding, attitudinal and linkage as challenging factors undermining effectiveness of work-based learning in Nigerian TVE. On the other hand, training, administrative, institutional and facility/curriculum are strategic factors for effectiveness of work-based learning in Nigerian TVE. Based on the findings, the study among others recommended strong technical and vocational education linkage with industry for skills training of students through work-based learning framework and approach